MENINGKATKAN KINERJA KARYAWAN MELALUI EXPECTANCY THEORY DALAM MOTIVASI - Teguh Suripto (Universitas Alma Ata, 2015)
Abstract Competition and economic growth has led many companies strive to improve its quality. Many efforts made by the company to improve its quality, including improving the process of production, did diversifying products, and motivating employees to improve performance. All of these efforts make a lot of companies have a lot to do an evaluation of His attempt. By understanding expectancy can be arranged planning employees good motivation, which can improve employee performance. Therefore learn Expectacy employees, as stipulated in the Expectancy Theory can help companies to plan and mapping motivation will be given to employees. Furthermore, how Expectancy Theory in motivation able to provide guidelines for the planning of motivation in the company? Is Theory expectancy implementation can improve the performance of employees in the company? Writing this using literature study, using journals and book library. The study concluded among other things, that an approach that can be used to megetahui what drives human beings is Expectancy Theory. This approach assumes that people will take action to achieve the goals that he considered valuable. Expectancy Theory is basically capable of providing employee performance improvement, because, in the provision of motivation, employees and leaders working to achieve the expected goals together, and also conduct a review and evaluation of the results. Keyword: Expectancy Theory, Motivation, Performance